Strategic Management of Microenterprises in the Cha-am and Hua Hin Districts - Jaroensombut, Lertlak (Journal for Developing the Social and Community, 2020)
This study’s objectives were to study the strengths, weakness, opportunities, threats to the business management, and management strategy of microenterprises in the Cha-am and Hua Hin districts. This study took on a qualitative method by conducting in-depth interviews of 40 microenterprises with accidental sampling and snowball sampling. It then applied content analysis and descriptive analysis to analyze the data. The study found that a strength is using little money for investment, a weakness is lacking skill and knowledge, and an opportunity is having a government policy that encourages more microenterprises. In addition, regarding strategic management, an entrepreneur should be service-minded, have good financial management, have an accounting system, and be able to think creatively.